The Influence of Sexual Arousal on Self-Reported Sexual Willingness and Automatic Approach to Models of Low, Medium, and High Prior Attractiveness. Issue 7 (1st September 2020) - Borg, Charmaine; Pawłowska, Aleksandra; van Stokkum, Robin; Georgiadis, Janniko R.; de Jong, Peter J.
ABSTRACT: Anecdotal evidence suggests that sexual attraction is flexible, and that high levels of sexual arousal can promote sexual willingness and approach tendencies toward a priori low attractive mates. This experimental study tested whether heightened sexual arousal can lower the threshold for sexual willingness and automatic approach tendencies toward potential sex partners of low and medium attractiveness. Heterosexual male ( n = 54) and female ( n = 61) participants were randomly assigned to a sexual arousal or control condition. Approach tendencies were indexed using a reaction time task. Sexual willingness was indexed using participant ratings of willingness to kiss and to consider having sex with same- and other-sex models of low, medium, and high attractiveness. Overall, participants showed stronger approach to models of high and medium than of low attractiveness. Sexual arousal weakened this differential responding but did not result in a robust increase of approach toward less attractive other-sex or same-sex models. Sexual willingness toward less attractive models was not affected by sexual arousal. Independent of condition, women reported greater sexual willingness toward same-sex models. The current pattern of findings does not support the notion that sexual arousal promotes automatic approach and sexual willingness to a broader array of sex partners.